USING QUOTATIONS TO MANIPULATE OUTCOMES IN TANZANIAN LEGISLATIVE DISCUSSIONS - Thompson, H; Alvarez, J. (Research Journal of Literature, Languages and Linguistics, 2024)
This article examines the use of strategic misquotation by Members of Parliament (MPs) during ministerial budget debates in the Tanzanian parliament. Grounded in pragmadialectics, the study focuses on the extent to which strategic misquotation can be manipulative and fallacious. Analysis of Hansard transcripts of parliamentary debates in Kiswahili based on annual ministerial budget speeches reveals that MPs employ strategic misquotation to manipulate their political opponents and the electorate. The article argues that strategic misquotation is fallacious when it manipulates the propositional content of the relevant quotation and constitutes a derailment of strategic manoeuvring. The study highlights that authority argumentation could be a reasonable argumentative move or a fallacious rhetorical strategy. Misquotations usually constitute manipulation of the actual quotations and could thus be fallacious. The article concludes by suggesting that MPs employ strategic misquotation to achieve various political motives in favour of their political group.